Ochrana hospodářské soutěže v České republice - Lánová, Hana (Univerzita Pardubice, 2006)
Práce se zabývá teoretickým vymezením pojmů, historickým vývojem včetně filozofických směrů, cílů, nositelů a nástrojů ochrany hospodářské soutěže. Druhá část je věnována zákonu č. 143/2001 Sb., o ochraně hospodářské soutěže, ve znění pozdějších předpisů a třetí část je zaměřena na dělbu kompetencí mezi Evropskou komisí a Úřadem pro ochranu hospodářské soutěže.

My bachelor work problems of Economic Competition Protection - notions, historical emergence with positivism, aims, wearers and instruments economic competition protection. In the second part I have engaged in Law for protection of competition and in the last part I have compared the division of competencies between the EU institutions, namely European Committee and the Office for Protection of Competition.
Economic competition protection in the Czech republic
Keywords: history; philosophy; competition protection; historie; koncepce; cíle; hospodářské soutěže; úřady